Getting On-The-Same-Page - Ali J. M. Summer (Grounded Theory Review: An International Journal)
Work teams are intrinsic to how 21st century organizations operate. For several decades, business research has therefore focused on work team performance. De Bono thinking tools have also been used extensively by work teams, for several decades. However, there is a paucity of research on the correct use of de Bono thinking tools in business organizations. The getting on-the-same-page classic grounded theory is therefore a new theory explaining what happens when work teams utilize these tools. The research problem was the main concern of people using de Bono thinking tools in this substantive area. The study revealed their concern is resolved with a three-stage process of change in personal cognitive capability. This process is fragile and can cease at any time. When it continues however, there are three stages of emergent change: tooling-up, tensing and enabling. Discovery of this process contributes to work team theory and praxis, particularly in the area of work team processes and effectiveness.